A Web-Based Breastfeeding Education Program - Cheng, Wei-Chen (Phoebe) (2003)
Two Web-based breastfeeding programs were developed to provide new parents with necessary information on proper breastfeeding techniques. One version was plain text and the other version combined text with graphics. The computer was viewed as a valuable learning tool. The breastfeeding program that contained graphics was preferred over the text-only program. Educators are encouraged to use Web-based graphic programs to provide breastfeeding education to new parents.